Effect of Feeding Green Yeast Culture on the Growth Performance of Hanwoo Steers - Theresia Galuh Wandita; Delgerzul Bataar; Najuma Joshi; Mugambe Julius; Seong Gu Hwang (International Journal on Food, Agriculture and Natural Resources, 2020)
To overcome the loss in terms of mortality and morbidity as the result of the restriction of in-feed antibiotics, many alternatives have been proposed. Yeast cultures as feed additives have various physiological activities in ruminants. Supplementing yeast makes it possible to stimulate the growth of specific rumen microorganisms which ultimately improves the growth of ruminants. This study was designed to analyze the potential effect of green culture, a feed supplement with fermented yeast, in growth performance and immune status of Hanwoo steers. A total of 30 animals were divided into two experimental groups: Control and Green Culture. For each group, five pens were used. Three 6 to 8 months old Hanwoo steers were housed per pen. In-vitro rumen fermentation by the green culture was done to generate base evidence to reflect the In-vivo field trial results. It was found out that, the average daily gain of the treatment group (0.93±0.04kg) supplemented with green culture was significantly higher (p-value less than 0.05) than that of the control group (0.84±0.10kg). In-vitro, ruminal fermentation analysis showed that the total volatile acid content increased with the addition of green yeast culture. These results suggested that the ruminal digestibility of nutrients improved which is reflected in the increase in body weight. Moreover, there was an increase of acetic acid production, in the treatment group supplemented with GC, which is reported to be related to the formation of lipid precursor cells. Therefore, green culture seems to improve the growth of Hanwoo steers as well as their meat quality.